The Economic Policy Agenda in Australia, 1962–2012 - Fenna, Alan (Blackwell Publishing Asia P/L, 2013)
This paper surveys Australian economic policy over the last half century, identifying patterns and punctuations in the management of both macroeconomic and more structural challenges. It highlights the extent to which the economic policy agenda has been dictated by economic forces, while acknowledging the ideological preferences governments bring to their task. In retrospect, this half century in Australia has been dominated by macroeconomic turmoil and structural adjustment in the middle decades. Australian governments had to deal simultaneously with the macroeconomic problems of inflation and recession from the mid-1970s to the early 1990s while also facing the need to dismantle the development framework that had been in place since Federation or even earlier.